Single-kernel near-infrared analysis for evaluating wheat samples for Fusarium head blight resistance - Peiris, Kamaranga; Dong, Yanhong; Bockus, William W.; Dowell, Floyd E. (My University, 2014)
This report describes a method to estimate the bulk deoxynivalenol (DON) content of wheat grain samples with the single-kernel DON levels estimated by a single-kernel near-infrared (SKNIR) system combined with single-kernel weights. The described method estimated the bulk DON levels in 90% of 160 grain samples to within 6.7 ppm of DON when compared with the DON content determined with the gas chromatography–mass spectrometry method. The single-kernel DON analysis showed that the DON content among DON-containing kernels (DCKs) varied considerably. The analysis of the distribution of DON levels among all kernels and among the DCKs of grain samples is helpful for the in-depth evaluation of the effect of varieties or fungicides on Fusarium head blight (FHB) reactions. The SKNIR DON analysis and estimation of the single-kernel DON distribution patterns demonstrated in this study may be helpful for wheat breeders to evaluate the FHB resistance of varieties in relation to their resistance to the spread of the disease and resistance to DON accumulation.
Keywords: Deoxynivalenol; Wheat; Fusarium head blight